Leading for results : transforming teaching, learning, and relationships in schools - Sparks, Dennis. 4 0 16; 5 (Thousand Oaks, CA :;[Oxford, Ohio] : Corwin Press ;;NSDC, 2007)
Provides guidance and tools for school leaders, showing how to develop self-awareness regarding values, feelings, and intentions and use that awareness to energize an organization and help individuals meet their potential.
Introduction : change ourselves to change organizations -- How to use this book -- Transformation through clarity and creation -- Use fundamental choices to create your life -- Clarify your intentions -- Establish stretch goals -- Identify multiple ways to achieve your goals -- Find the trim tab -- Apply the 80/20 principle -- Practice satisficing -- Determine root causes -- Develop a theory of action and use storytelling to communicate it -- Gain clarity through writing, speaking, and reflecting on action -- Provide teachable points of view -- Transformation through interpersonal influence -- Tell your truth -- Use candor to assess current reality -- Use genuine dialogue -- Engage in dialogue-like conversations -- Listen to others in a deep, committed way -- Use stillness and silence as learning tools -- Make requests to initiate action and create results -- Make and keep promises -- Reduce question asking, increase declarative statements -- Minimize the language of obligation -- Decrease the use of cause-effect language -- Stand up for your point of view -- Transformation through a culture that promotes professional learning, teamwork, and continuous improvement -- Shape school culture to improve teaching and sustain competent teachers -- Create successful schools -- Promote breakthrough thinking -- Attend to leaders' inner development -- Recognize our best selves -- Increase the use of signature strengths -- Enhance your personal energy -- Build relationships to sustain positive energy -- Address the fundamental barriers to professional learning and teamwork in schools -- Spread positive emotions throughout the organization -- Address anxiety in the schoolhouse -- Appeal to the heart as well as the head -- Transformation through professional learning and doing -- Design powerful professional learning for all educators -- Match professional development goals and methods with student outcomes -- Bridge the knowing-doing gap -- Amplify positive deviance in schools -- Create professional learning that alters educators' brains -- Install next action thinking -- Change habits -- Sustain the conversation.
Includes bibliographical references and index.
Professional;Professional
Keywords: 2 -- 0; 6; Administration. -- School management and organization.;Educational leadership.;Schools;Educational leadership; 20; 2